Clustering of multiple health risk behaviours and association with socio-demographic characteristics and psychological distress among adolescents in Ghana: A latent class analysis. (March 2021) - Atorkey, Prince; Owiredua, Christiana
Abstract: This study examined the prevalence of multiple health risk behaviours, the clustering patterns of health risk behaviours, the association between socio-demographic characteristics, psychological distress and clusters and the relationship between number of health risk behaviours and psychological distress among adolescents in Ghana. Participants were senior high school (SHS) students aged 11–19 years who participated in the 2012 Global School-based Students Health Survey (n = 1763). Five health risk behaviours (smoking tobacco, inadequate fruit intake, inadequate vegetable intake, alcohol intake and physical inactivity) were measured. Participants were classified to be at risk if they indicated they smoked tobacco, did not eat fruit ≥ 2 times a day and vegetables ≥ 5 a day, drank alcohol during the past 30 days and did not engage in physical activity for ≥ 60 min per day during the past 7 days. Latent class analysis and latent regression were used to identify the clusters and factors associated with the clusters respectively. Multiple logistic regression was used to determine the relationship between number of health risk behaviours and psychological distress. The prevalence of multiple health risk behaviours (2 or more) was 94.8%. Two clusters emerged: Cluster 1 ("Poor nutrition, inactive, low substance use cluster"; 91%); Cluster 2 ("High Risk Cluster"; 9%). Using cluster 1 as a reference group, adolescents in the 11–15 years category had lower odds of belonging to cluster 2 (OR = 0.21 CI 0.05–0.91, ρ = 0.036) while those experiencing symptoms of depression had higher odds of belonging to cluster 2 (OR = 2.45 CI 1.45–4.14, ρ = 0.001). No significant relationship was found between number of health risk behaviour and psychological distress. Health risk behaviours cluster among adolescents with age and depression associated with the identified clusters. Early interventions that target these clusters are needed at the individual, school and community level to mitigate the burden of non-communicable diseases. Highlights: Prevalence of multiple health risk behaviours among adolescents in Ghana is high. Multiple health risk behaviours cluster among adolescents in Ghana. Some demographic and psychological factors are associated with clusters among adolescents.